Influence of prepreg parameters on the interlaminar consolidation of fiber reinforced thermoplastic laminates manufactured by vacuum-bag-only process - Saffar, Florence; Beauchêne, Pierre; Sonnenfeld, Camille; Park, Chung Hae (Frontiers in Materials, 2022)
To better understand the influence of the prepreg parameters such as surface roughness, fibres/matrix distribution (e.g. presence or absence of pure matrix layer on the prepreg surface) and initial matrix crystallinity, two different carbon fibres/PEKK (Poly-Ether-Ketone-Ketone) prepreg are used to fabricate unidirectional laminated by vacuum bag only (VBO) process. By an in-situ monitoring set-up, the laminate thickness and the temperature difference along the thickness direction are measured throughout the consolidation cycle. The quality of laminate is assessed in terms of interlaminar shear strength and void content evaluation. A finite element model has been developed to describe the intimate contact phenomenon by the deformation of surface roughness between the glass transition temperature and the melting temperature of the matrix. In particular, the real profile of surface roughness of prepreg was adopted and the variable Young’s modulus of matrix in terms of temperature and crystallinity was implemented as the input data in the numerical simulation. Finally, the high influence of the matrix crystallinity degree and the surface roughness on the intimate contact phenomenon are highlighted.